Current biomechanical methods and practices of physical training load monitoring in women`s artistic gymnastics: a scoping review - Boylen, A. M.; Campbell, R. A.; Drinkwater, E. J.; Bradshaw, E. J. (Journal of Sports Sciences, 2025)
Women`s artistic gymnastics (WAG) is a precision-based sport involving intense physical and technical training from a young age. Injuries in WAG can be a result of poorly managed acute and/or chronic biomechanical loads. This scoping review aims to identify current biomechanical methods of load monitoring in WAG. This review followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). Four databases (MEDLINE, Scopus, Web of Science, SPORTDiscus) were searched for studies that measured biomechanical load of competitive WAG skills. Sixteen studies met the inclusion criteria from the previous 15 years. Biomechanical load was measured using force plates and/or inertial measurement units (IMU). Only three studies have used IMUs in WAG, however they are a more ecologically valid method for monitoring load during training sessions and have shown that technique/skill variations affect the biomechanical load gymnasts experience. Upper limb asymmetries exist in common WAG skills; therefore, opposite limbs may have different injury risks. No studies investigated biomechanical load of uneven bars, and few measured skills on unmodified, competition apparatus. Comprehensive understanding of loads gymnasts experience is essential for effectively managing training prescription and injury prevention strategies.